The dynamics of empathy within participatory design pedagogy and practice - Ruijsch Van Dugteren, Jill (School of Education, 2014)
The nature of this qualitative study has been guided by my goals to firstly explore a framework for design, and design education, that attempts to alleviate and not exacerbate complex social problems, many of which can be seen to stem from a lack of empathy and accountability. These act to isolate and invalidate our interactions within a broader web of relations - with others, with the environment, and also with our selves. Secondly, I wanted to explore the changing role of the designer in grappling with these challenges, which necessitate by their complex nature, interdisciplinary collaboration. And thirdly, I wanted to explore beyond the familiar comfort zone of my own design education practice in order to improve and expand upon it. Participatory Design is significant here, as it provided a design methodology and lens, which both addressed the above goals and theoretically grounded the accountability and responsibility of the designer. Through their access to key platforms of mass communication and production, designers inadvertently and persistently, become both educators and influencers whose capacity and reach will exponentially magnify the brief contact they have experienced studying design at tertiary level. This draws into sharp focus both the key moral imperative that educators continue to gravitate towards, but also the role that empathy plays here. What is lacking, and what this research seeks to address is the manner in which we are not only distinct cognitive and affective 'components', but that we empathically connect, and participate both in the world and with design, through our bodies and our interactions. This study explores how the dynamic of empathy is embodied, enacted and expressed within Participatory Design pedagogy and practice.